(untitled) (Revista de Investigaciones Universidad del Quindío, 2020)
Protestantism spread and developed in the Hmong community in Northwestern Vietnam has changed many aspects in the socio-cultural life of the Protestant Hmong in particular and some other ethnic minorities in the Northwest in general. Along with the rapid development of Protestantism in the Northwest, a Protestant Hmong community with a culture and lifestyle that is different from the rest of the Hmong community has been formed. Under the influence of Protestantism, family, lineage and village relationships of this Protestant Hmong community have been gradually changed in many aspects as well. This transformation has had a positive impact on the lives of the Hmong people but also poses many challenges for preserving the cultural identity of the Hmong ethnic in Northwestern Vietnam today.